Bilateral anterior lenticonus in a patient with Alport syndrome – a case report - Brymerski, Jacek; Wietrzykowska, Katarzyna; Olszewski, Mateusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
The article presents a case of a bilateral anterior lenticonus in a 28-year-old patient with Alport syndrome. Alport syndrome is an inherited condition characterized by progressive renal failure, hearing loss, and ocular abnormalities, due to mutations in the COL4A3–5 genes, which result in absence of the collagen alfa–IV. Homozygote males are usually severely affected but females tend to have a mild form. Anterior lenticonus occurs in approximately 50% patients with Alport syndrome. It manifests as progressive deterioration of vision due to progressive myopia, and astigmatism, requiring frequent changes in spectacle prescription. Clear lens phacoemulsification with foldable intraocular lens implantation is a safe and efficient procedure in the anterior lenticonus secondary to Alport syndrome.